2019
DOI: 10.1155/2019/7462940
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Nutrition Coverage in Outpatient Cancer Centers: Results of a National Survey

Abstract: Cancer-related malnutrition is associated with poor health outcomes, including decreased tolerance to cancer therapy, greater treatment toxicities, and increased mortality. Medical nutrition therapy (MNT) optimizes clinical outcomes, yet registered dietitian nutritionists (RDNs), the healthcare professionals specifically trained in MNT, are not routinely employed in outpatient cancer centers where over 90% of all cancer patients are treated. The objective of this study was to evaluate RDN staffing patterns, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 48 publications
4
84
0
3
Order By: Relevance
“…RDNs are uniquely trained to address malnutrition and can provide the individualized nutrition counseling and MNT needed, but they are inadequately staffed in cancer centers. A recent study found that the RDN-to-patient ratio in U.S. oncology centers is 1:2308 [50]. Indeed, only half (53.1%) of oncology centers screen for malnutrition, and a majority (76.8%) of these centers do not bill for nutrition services [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RDNs are uniquely trained to address malnutrition and can provide the individualized nutrition counseling and MNT needed, but they are inadequately staffed in cancer centers. A recent study found that the RDN-to-patient ratio in U.S. oncology centers is 1:2308 [50]. Indeed, only half (53.1%) of oncology centers screen for malnutrition, and a majority (76.8%) of these centers do not bill for nutrition services [50].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that the RDN-to-patient ratio in U.S. oncology centers is 1:2308 [50]. Indeed, only half (53.1%) of oncology centers screen for malnutrition, and a majority (76.8%) of these centers do not bill for nutrition services [50]. The recently introduced US Medical Nutrition Therapy Act of 2020 (H.R.…”
Section: Discussionmentioning
confidence: 99%
“…The Academy, in describing their first ever malnutrition eCQMs, recognized the availability of these eCQMs as a “tremendous opportunity to advance patient/client nutrition care.” They further underscored that “the development of the eCQMs and tools to support implementation is one of the most innovative initiatives undertaken by the Academy of Nutrition and Dietetics” [ 62 ]. Consistent malnutrition screening is critical for the early identification and treatment of malnutrition; however, in a survey of U.S. ambulatory oncology settings, only about half reported screening for malnutrition [ 12 ]. Targeting the development of malnutrition quality measures specific to cancer care should be a priority for nutrition and oncology organizations because eCQMs are an effective tool to help identify where malnutrition screening is not occurring as well as to document the burden of malnutrition and the positive outcomes that are realized when malnutrition is better identified and treated.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the American outpatient setting, where nearly all oncology patients receive treatment, ambulatory nutritional care standards and interventions for cancer are ambiguous and inconsistently applied [10]. This is further complicated by the fact that registered dietitian nutritionists (RDNs) are not routinely employed in outpatient cancer centers and the medical nutritional therapy that they provide is not consistently a part of multidisciplinary outpatient cancer care or adequately reimbursed [12]. The lack of systematic malnutrition screening and intervention in ambulatory cancer care has especially significant consequences for both patient and healthcare outcomes and thus the nutrition support of patients with cancer represents an important area for quality improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there will be some degree of ‘hit-and-miss’, which patients (and professionals) will need to experiment with. If available and affordable, a professional dietician with expertise in the cancer area could also help improve the patient survival rate [ 357 ]. Thus, integrated management may work better on some patients than others.…”
Section: Future Perspectivesmentioning
confidence: 99%